2014
DOI: 10.1590/s0100-204x2014000400006
|View full text |Cite
|
Sign up to set email alerts
|

Reguladores de crescimento na frutificação efetiva e qualidade de frutos partenocárpicos de atemoia 'Gefner'

Abstract: Resumo -O objetivo deste trabalho foi avaliar os efeitos de reguladores de crescimento vegetal sobre a frutificação efetiva e a qualidade de frutos partenocárpicos de atemoia 'Gefner'. O experimento foi realizado em pomar de atemoia 'Gefner', em Homestead, Flórida, EUA. Utilizou-se um delineamento experimental de blocos ao acaso, com quatro tratamentos, cinco repetições e seis flores por parcela. Os tratamentos foram compostos por: T1, ácido naftaleno acético a 450 mg L -1 e ácido giberélico a 1.000 mg L -1 ; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Similar behavior was observed in Homestead, South Florida. 'Gefner' custard apple flowers treated with 1,000 ppm GA 3 at anthesis and at the 1 st , 3 rd and 5 th WAA without hand pollination (HP) presented an average of 80% fruit set by fruit harvest at the 19 th WAA (Pereira et al, 2014). Another study also showed that the number of applications of plant-growth regulators affects the fruit set.…”
Section: Fruit Setmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar behavior was observed in Homestead, South Florida. 'Gefner' custard apple flowers treated with 1,000 ppm GA 3 at anthesis and at the 1 st , 3 rd and 5 th WAA without hand pollination (HP) presented an average of 80% fruit set by fruit harvest at the 19 th WAA (Pereira et al, 2014). Another study also showed that the number of applications of plant-growth regulators affects the fruit set.…”
Section: Fruit Setmentioning
confidence: 99%
“…Similar results were observed by Saavedra (1979), Yonemoto et al (2004) and Pino (2008), who also found high rates of parthenocarpic fruits in cherimoya. According to Pereira et al (2014), the use of 1,000 ppm GA 3 resulted in 80 % seedless fruits in the 'Gefner' custard apple, and when applied to pollinated fruits, this same dose resulted in the lowest seed number/100 g of fruit and pulp ratio. No significant differences were observed among the treatments for the percentage of fruit pulp, ranging from 64.2 to 73.9 % (Fig 4).…”
Section: Physical and Chemical Characteristics Of The Fruitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of plant hormones on fruit production has shown positive results in relation to the increase of the physical variables on pitayia (NOR et al, 2014), inhibition of maturation and extension of the postharvest of bananas (HUANG;JING, 2012), and improving of physiochemical characteristics of apples (YILDIZ et al, 2012). Among the plant regulators used in postharvest of fruits, gibberellic acid (GA 3 ) exerts a great influence on the quality and extension of postharvest of grapes (MARZOUK; KASSEM, 2011) and fruiting of atemoieira (PEREIRA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%